Organización Contable en la Ferretería Innovaled del Cantón Catamayo periodo 2023. - Ambuludí Jumbo, María José (2024)
Micro, small, and medium enterprises (MSMEs) are the main support for most economies, playing a crucial role in global economic development and being fundamental to job creation. However, despite their potential contributions, MSMEs face significant limitations in their survival and future sustainability. As a result, only 64% survive their first year of operation, and barely 50% manage to remain in the market for more than five years. Among the factors contributing to their decline or collapse are inadequate and ineffective accounting practices. This is why the objective of the present research is to organize the accounting of Ferretería Innovaled in the canton of Catamayo, Province of Loja, for the period from October 1 to December 31, 2022. A mixed methodology was applied to achieve this goal. In the qualitative phase, a plan and manual of accounts were developed, and in the quantitative phase, main and auxiliary formats for the accounting process were designed. The results indicate a notable improvement in accounting organization and the accuracy of financial records. Additionally, the adoption of specific accounting formats has optimized resource management and increased the company's operational transparency. It is recommended that the company utilize advanced software, conduct periodic internal audits, establish an internal control system, train staff in basic accounting, adopt data analysis tools, and develop a financial contingency plan.